Proposta de sistematização pedagógica e avaliação no handebol em cadeira de rodas - Oliveira, Ana Carolina Santana de (2011)
The adapted sport has spread within adapted physical education and among people with disabilities, given the range of possibilities it offers. The wheelchair handball (WH) is a sport still not very popular, even among people with physical disabilities and has been worked out recently by some professionals in Adapted Physical Education. Due to the fact that it is a new modality and it is still in a phase of construction of knowledge, there are few academic studies related to HW. This research had the aim of filling the blanks that exist in the pedagogical approach of the modality, thus supplying academic support for the future teachers who intend to teach it. Therefore, the aim of the present research was to systematize, apply and describe the program of pedagogical intervention of handball in wheelchairs for disabled people describing its main fundaments. The specifics objectives were: to evaluate the evolution of the abilities in the execution of the sport fundaments in the periods before and after intervention and evaluate in which fundaments the disabled athletes which participated in the study obtained better results. The research was carried out using the experimental methodology, by using the intra-subjects outlining (pre and post test) and AB outlining. The study included four people with physical disabilities, three men and one woman. The data were collected for 12 weeks with 2 sessions in a week (total of 24 sessions, 4 sessions of baseline and 20 intervention sessions) in a city in the state of São Paulo / SP, with all sessions filmed. The data collection was carried out through a protocol of record of task analysis, previously established by the researcher. The analysis was made by three researchers and presented in a qualitative (descriptive) and quantitative way, with statistical analysis (paired t test, considering p <0.05). The analyzed results have margin to select the main fundaments of the WH (handling and displacement with the wheelchair, conduction and control of the ball, throwing, passing and catching the ball, dodging and positioning in the court) and with intervention, we can infer that all the grounds, without exception, displayed an increase of the scores obtained by the athletes, and the fundaments that had the highest scores were exclusive of handball - passing and catching the ball and throwing and the fundament that was less evolution was dodging. This research gave rise to infer that the intervention was effective in promoting the learning of the HW by the participants, and the instrument constructed, it can be applied to other athletes to evaluate the learning of the modality fundaments.